Pelatihan Smart Home dengan Smart Control untuk Instalasi Listrik Berbasis Wifi - Oriza Candra; Syaiful Islami; Nevi Faradina; Syamsuarnis Syamsuarnis; Elfizon Elfizon; Hendri Hendri (Jurnal Teknik Elektro Indonesia, 2022)
Skills training on smart home electric lighting installations to provide skills for students and teachers of the State 1 Buo Vocational High School (SMK) in installing and repairing smart home electrical installations independently in addition to knowledge and skills about wifi networks. This service is carried out at SMKN 1 Lintau Buo because there is no supporting equipment and do not have knowledge about electrical installations in smart home systems. With this activity, it is expected that students and teachers have knowledge of electric lighting installations. This training is given in two stages, the first stage is material provision and the second stage is material testing, both theoretically and theoretically. This provides effectiveness for increasing training competence by 81% of participants in understanding the installation of smart home electric lighting, reading installation drawings, measuring voltage, detecting broken connections, and being able to set up smart home installation equipment. In general, this has been able to improve the skills of students and teachers of the State Vocational High School 1 Lintau Buo.